A case of severe COVID-19 with pulmonary thromboembolism related to heparin-induced thrombocytopenia during prophylactic anticoagulation therapy. Issue 8 (August 2022) - Sasaki, Kosaku; Murata, Masayuki; Nakamura, Keiji; Matsumoto, Yuji; Nakashima, Yuko; Yamasaki, Sho; Ota, Azusa; Hiramine, Satoshi; Takayama, Koji; Ikezaki, Hiroaki; Toyoda, Kazuhiro; Ogawa, Eiichi; et al.
Abstract: A 53-year-old male Japanese patient with COVID-19 was admitted to our hospital after his respiratory condition worsened on day 9 of the disease. With the diagnosis of severe COVID-19, treatment with remdesivir, dexamethasone, and unfractionated heparin was started for the prevention of thrombosis. Although the patient's respiratory status data improved after treatment, severe respiratory failure persisted. Thrombocytopenia and D-dimer elevation were observed on day 8 after heparin therapy initiation. Heparin-induced thrombocytopenia (HIT) antibody measured by immunological assay was positive, and contrast computed tomography showed pulmonary artery thrombus. The patient was diagnosed with HIT because the pre-test probability score (4Ts score) for HIT was 7 points. Heparin was changed to apixaban, a direct oral anticoagulant, which resulted in a reduction of the pulmonary thrombus and improvement of the respiratory failure. In patients with COVID-19, anticoagulant therapy with heparin requires careful monitoring of thrombocytopenia and elevated D-dimer as possible complications related to HIT. (151/250 words).